THE INFLUENCE OF EDUCATION, POPULATION GROWTH, UNEMPLOYMENT, AND INCOME INEQUALITY ON THE PERCENTAGE OF POOR POPULATION IN REGENCIES/CITIES IN PAPUA PROVINCE - Solfitri; I Wayan Priyana Agus Sudharma (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Poverty is a multidimensional issue in development, as addressing it involves challenges that go beyond the causal relationships underlying poverty. It also entails considerations of preferences, values, and politics. This study aims to analyze the simultaneous and partial effects of education, population growth, unemployment, and income inequality on the percentage of the poor population in Papua Province. The data used in this research is secondary data from 2017 to 2021, covering 29 regencies/cities in Papua Province. The data analysis technique employs panel data regression using the Eviews 12 software. The results of the study show that education, population growth, unemployment, and income inequality simultaneously influence the percentage of the poor population in regencies/cities in Papua Province. Furthermore, it is found that, partially, the variables of education, population growth, and unemployment have a negative and significant effect, while the income inequality variable has a positive and significant effect on the percentage of the poor population in the regencies/cities of Papua Province.